Answer :

Solve is in the picture

Good luck :)
${teks-lihat-gambar} Nümerik
Solutions 

Simplifying
3x + -3(2x + -2) = -3 

Reorder the terms:
3x + -3(-2 + 2x) = -3
3x + (-2 * -3 + 2x * -3) = -3
3x + (6 + -6x) = -3
Reorder the terms:
6 + 3x + -6x = -3 

Combine like terms:
3x + -6x = -3x
6 + -3x = -3

Solving
6 + -3x = -3 

Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right. 

Add '-6' to each side of the equation.
6 + -6 + -3x = -3 + -6

Combine like terms: 6 + -6 = 0
0 + -3x = -3 + -6
-3x = -3 + -6

Combine like terms: -3 + -6 = -9
 -3x = -9

Divide each side by '-3'.
 x = 3
 
Simplifying
x = 3

Other Questions